Heuristic Biases and Investment Decision-Making: The Mediating Role of Risk Attitude in an Emerging Market Context - Hasanka, N.W.A.D.; Tharshiga, P. (Sri Lanka Finance Association, 2025)
An individual's decision-making is not solely based on rational evaluation but is strongly influenced by psychological and behavioural factors. Heuristic biases, such as anchoring, availability, and representativeness, are central to shaping how individuals perceive financial opportunities and risks. While these prejudices have been extensively studied in developed economies, there is a lack of empirical evidence within emerging market contexts, particularly at the regional level in Sri Lanka. The present study, therefore, examines the influences of heuristic biases on investment decision-making, with special attention given to the mediating role of risk attitude among individual investors in the Anuradhapura District. The study adopted a quantitative research design, drawing on data collected through a structured questionnaire administered to individual investors. A proportionate sampling approach ensured fair representation across divisions. Data was analyzed using Partial Least Squares Structural Equation Modelling techniques that allowed both the measurement model and the structural relationships to be tested. The analysis confirmed that the constructs were reliable and valid, and the overall model was suitable for further interpretation. The study's findings reveal that anchoring bias plays a significant role in directly shaping investment decisions. In contrast, availability and representativeness biases did not show a significant direct influence on investment decisions. However, all three heuristic biases affect risk attitude, which emerges as a strong predictor of investment decision-making. Mediation analysis further highlights that risk attitude acts as a full mediator for availability and representativeness, and as a partial mediator for anchoring. These results demonstrate that the psychological orientation of investors toward risk is a critical pathway through which cognitive shortcuts influence financial behaviour. In conclusion, this study demonstrates that the interplay of heuristic biases and psychological factors shapes investment decisions in emerging markets. By highlighting the central role of risk attitude, it underscores the need to integrate behavioural perspectives into academic research and practical approaches to financial decision-making.
Keywords: Anchoring bias; Availability bias; Heuristic biases; Representativeness bias; Investment decision making